Influence of okra (Abelmoschus esculentus) genotypes on growth, yield and biochemical traits - KOHIMA NOOPUR; R K SAMNOTRA; S KUMAR (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted at vegetable research farm of Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu, Jammu and Kashmir (J&K) during 2019–21 to evaluate the performance of 8 improved genotypes of okra (Abelmoschus esculentus L. Moench) and compare them with the popular check genotype in terms of yield attributes and yield, quality and biochemical traits. Among the okra genotype, DOV-44≥Punjab Padmani≥Kashi Kranti produced significantly (P<0.05) higher pod weight as compared to the remaining cultivars and recorded an improvement of 10.7–16.4% for pod weight over the local check (Parbhani Kranti). DOV-44 ≥Punjab Padmani ≥Kashi Kranti produced 110.7–120.1% higher okra pod yield over the check (Parbhani Kranti) averaged over the years. Significant positive correlation of yield attributes like days to 50% flowering (r= 0.5294*, P<0.05) leaf length (r= 0.8217**, P<0.001), pod length (r= 0.6863*, P<0.05), pod diameter (r= 0.7866*, P<0.05) and pod weight (r= 0.8417**, P<0.001) with okra pod yield also affirmed it better performance as compared to local check. Among the cultivars, chlorophyll A among the cultivars also varied significantly (P<0.05) from 7.26 in DOV-88 to 5.13 in Pusa Bhindi-5. Calcium content was observed highest in Kashi Kranti (93.67) ≥ DOV-88 (92.00) and it was 21.5–23.8% higher than local check (Parbhani Kranti). The genetic make-up responsible for higher growth, better physiological and biochemical attributes may help in improving adaptive capacity for achieving optimal productivity. Thus, exploring improved genotypes suitable to J&K ecosystem promises improvement of okra productivity along with maintaining better biochemical traits in the J&K of India and other similar agro-ecological regions.